Characterization of Fusarium Spp. Inciting Vascular Wilt of Tomato and Its Management by a Chaetomium-Based Biocontrol Consortium - Pothiraj, Govindan; Hussain, Zakir; Singh, Awani Kumar; Solanke, Amolkumar U.; Aggarwal, Rashmi; Ramesh, Raman; Shanmugam, Veerubommu (Frontiers in Plant Science, 2021)
Vascular wilt of tomato caused by species of Fusarium though globally reported to be a complex disease in certain countries, in India, our studies indicated that the disease is caused by either Fusarium oxysporum f.sp. lycopersici (Fol) or Fusarium solani (FS) with the Fol being widely prevalent. In assessing the genetic diversity of 14 Fol strains representing four Indian states by unweighted pair group method with arithmetic averaging using Inter Simple Sequence Repeat amplicons, the strains distinguished themselves into two major clusters showing no correlation with their geographic origins. In pot experiments under polyhouse conditions, seed dressing and soil application of a talc-based formulation of a biocontrol treatment, TEPF-Sungal-1 (Pseudomonas putida)+S17TH (Trichoderma harzianum)+CG-A (Chaetomium globosum), which inhibited Fol was equally effective as the cell suspensions and was even better than the fungicidal mixture (copper oxychloride-0.25%+carbendazim-0.1%) in promoting the crop growth (52.3%) and reducing vascular wilt incidence (75%) over the control treatment, despite challenge inoculation with the highly pathogenic TOFU-IHBT strain. This was associated with significant expressions of the defence genes, indicating the induction of host resistance by the biocontrol consortium. In field experiments on two locations, the bioconsortium was highly effective in recording maximum mean fruit yields (54.5% & 60%) and minimum mean vascular wilt incidence (37.5%) in comparison to the untreated control. Thus, the Chaetomium based bioconsortium demonstrated consistency in its performance across two experiments in two years under two field conditions.